Influence of Different Cooking Methods on the Antioxidant Activity of Local Pumpkin Variety (Cucurbita maxima) Cultivated in Jaffna District - Thanuja, S.; Sivakanthan, S.; Vasantharuba, S. (University of Jaffna, 2018)
Antioxidants play major role in maintaining good health. Pumpkin (Cucurbita maxima) is one of the richest sources of β-carotene, a powerful antioxidant. However, the antioxidant activity of vegetables is influenced by the cooking methods. Therefore, this study aimed to determine the effect of three cooking methods on the antioxidant properties of pumpkin. The antioxidant properties such as total flavonoid content (TFC), total phenolic content (TPC), antioxidant capacity and antioxidant activity [2, 2-Diphenyl-1-picrylhydrazyl (DPPH), radical scavenging activity expressed as IC50 value] were determined. Fresh pumpkin was cut into small pieces and subjected to different cooking methods (boiling, microwave cooking and stir-frying) until pumpkin became tender and palatable. Ethanol (70 %, v/v) was used as the solvent to extract antioxidants. Higher loss of TPC was observed during stir-frying than microwave cooking and boiling. The highest TFC obtained from boiled sample compared to microwave cooked and stir-fried samples. Microwave cooking minimally destroyed antioxidant capacity than stir-frying and boiling compared to fresh pumpkin. Fresh pumpkin showed significantly lower IC50 than microwave cooked and stirs fried pumpkin. Boiled pumpkin showed the lowest DPPH radical scavenging activity. From this study, it can be concluded that, even though all three cooking methods studied have significant effect on antioxidant activity of pumpkin, microwave cooking has less effects on antioxidant activity than boiling and stir-frying
Keywords: Cooking; free radical scavenging activity; pumpkin; total flavonoid content; total phenolic content